Stimulation of adenovirus replication in simian cells in the absence of a helper virus by pretreatment of the cells with iododeoxyuridine. - Jerkofsky, M (1975)
Pretreatment of African green monkey kidney cells with 50 mu g of 5'-iododeoxyruidine (IUdR) per ml can modify their susceptibility to the replication of human adenovirus type 7 in the absence of simian virus 40 (SV40) although this enhancement of adenovirus replication is not as efficient as that of the helper SV40 virus. Since the number of infectious centers remains unchanged after IUdR pretreatment whereas the burst size of virus from each infected cell increases, the IUdR appears to allow each infected cell to produce more virus. Cell DNA synthesis appears to be stimulated in IUdR pretreated cells infected with adenovirus 7, but the host cell DNA synthesized is small enough to remain in the Hirt supernatant fluid. The modification of susceptibility to adenovirus replication and the changed pattern of cell DNA synthesis is stable for at least two additional cell passages of the pretreated cells.